2007
DOI: 10.1111/j.1529-8817.2007.00353.x
|View full text |Cite
|
Sign up to set email alerts
|

BACTERIAL LYSIS OF AUREOCOCCUS ANOPHAGEFFERENS CCMP 1784 (PELAGOPHYCEAE)1

Abstract: Water samples from Great South Bay, New York, contained biological agents capable of causing the lysis of the brown‐tide alga Aureococcus anophagefferens Hargraves et Sieburth. From these water samples, 32 bacterial isolates were tested for algicidal effects against the algae. Six of the isolates were shown to have algicidal effects against A. anophagefferens. Sequencing of the gene 16S rRNA revealed that the isolates were relatively diverse. Based on their similarity to sequences in repositories, the isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…RCC 80; moderate inhibition was observed with two distantly related diatoms T. pseudonana and T. oceanica and no inhibition was observed with T. weissflogii (Table 1). Frazier et al (2007) found that the pelagophyte Aureococcus anophagefferens was also inhibited by an isolate of C. atlanticus from Figure 1 Effect of three different C. atlanticus isolates on the growth rates of P. multiseries IOES-1. The growth rates of P. multiseries are indistinguishable from each other when 0.05% v/v of either fresh MB media (n = 2) or an overnight grown culture of Marinobacter sp.…”
Section: Resultsmentioning
confidence: 99%
“…RCC 80; moderate inhibition was observed with two distantly related diatoms T. pseudonana and T. oceanica and no inhibition was observed with T. weissflogii (Table 1). Frazier et al (2007) found that the pelagophyte Aureococcus anophagefferens was also inhibited by an isolate of C. atlanticus from Figure 1 Effect of three different C. atlanticus isolates on the growth rates of P. multiseries IOES-1. The growth rates of P. multiseries are indistinguishable from each other when 0.05% v/v of either fresh MB media (n = 2) or an overnight grown culture of Marinobacter sp.…”
Section: Resultsmentioning
confidence: 99%
“…HABs constitute a serious environmental threat to estuarine and coastal ecosystems, and several physical-chemical methods have been proposed to control and mitigate these events (e.g., clay flocculation, Sengco and Anderson, 2004). However, the repercussions of these control strategies still remain a concern (Frazier et al, 2007). Bivalve mollusks, namely native species, have also been…”
Section: Biologic Control Of Dissolved Organic Mattermentioning
confidence: 99%
“…Both experimental approaches and field studies have shown that phagotrophic protists may be responsible, to some extent, for the dissipation or absence of harmful phytoplankton blooms in inland, estuarine, and coastal areas (Jeong and Shim, 1996;Calbet et al, 2003;Rosetta and McManus, 2003;Gobler et al, 2007;Jeong et al, 2008;Stoecker et al, 2008). Other biologic processes, namely viral-, bacterial-and eukaryotic-induced lyses may also contri bute to the demise of HABs (Hare et al, 2005;Frazier et al, 2007;Montagnes et al, 2008b;Smayda, 2008).…”
Section: Biologic Control Of Biological Contaminantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest 16S rRNA gene sequence similarity to other validly published species was only 90.6%, which was recorded for Leeuwenhoekiella palythoae (8). Based on the results of polyphasic taxonomy, this bacterium was established as the type species of the genus Croceibacter in the family Flavobacteriaceae, an abundant marine bacterial group well-known for interaction with phytoplankton (2,4,6). The genome sequence of C. atlanticus HTCC2559 T (10) was shown to encode a protease showing algicidal activity as well as many proteins related to degradation of macromolecules such as alginate (12).…”
Section: Roceibacter Atlanticus Htcc2559mentioning
confidence: 99%